1996
DOI: 10.1136/gut.39.6.846
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis: a retrospective study of clinical presentation and treatment in 163 patients.

Abstract: Background-Data on collagenous colitis have been based on a limited number of patients. Aims-To obtain more information on this disease from a register set up at Orebro Medical Center Hospital. Patients and methods-Twenty five Swedish hospitals have contributed to this patient register, which comprises 163 histopathologically verified cases. Clinical data were retrospectively analysed. Results-Collagenous colitis followed a chronic intermittent course in most cases (85%) with a sudden onset in 42%. Symptoms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
394
2
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(435 citation statements)
references
References 27 publications
(11 reference statements)
22
394
2
17
Order By: Relevance
“…These figures are in agreement with two Swedish retrospective reports by Mellander et al [6] or Bohr et al [7] who reported that 2.1 and 1.8% of MC patients had concomitant or delayed IBD and MC diagnoses, respectively. Along the same line, five out of 790 IBD patients (0.6%) developed MC after the IBD diagnosis in the IBD Cohort of Uppsala Health Region (ICURE) study [8].…”
Section: Linkage Between Ibd and MCsupporting
confidence: 92%
“…These figures are in agreement with two Swedish retrospective reports by Mellander et al [6] or Bohr et al [7] who reported that 2.1 and 1.8% of MC patients had concomitant or delayed IBD and MC diagnoses, respectively. Along the same line, five out of 790 IBD patients (0.6%) developed MC after the IBD diagnosis in the IBD Cohort of Uppsala Health Region (ICURE) study [8].…”
Section: Linkage Between Ibd and MCsupporting
confidence: 92%
“…Although a female preponderance has been reported in MC, especially in collagenous colitis, (11)(12)(13)(14), recent reports show that this remains controversial (3). Zins et al reported no significant gender differences for collagenous colitis or lymphocytic colitis (15).…”
Section: Du Od E N a L B I O P S Y S H O We D I N F L A Mma T I O N Wmentioning
confidence: 98%
“…На примере большой популяции из 163 пациентов с КК I. Bohr и соавт. [56] определили следующую частоту симптомов: ночная диарея (27%), снижение массы тела (42%), боли в животе (41%), усталость (21%) и метеоризм (12%).…”
Section: терапевтический архив 4 2015unclassified
“…В ретроспективных исследованиях показана эффективность ло-перамида в дозе от 2 до 16 мг/сут, однако стойкая клиническая ремиссия при его применении развивается редко [17,34,56].…”
Section: терапевтический архив 4 2015unclassified